Which publics? When? Exploring the policy potential of involving different publics in dialogue around science and technology. - Mohr, Alison; Raman, Sujatha; Gibbs, Beverley (Sciencewise-ERC, 2013)
How should we understand ‘the public’ in public dialogue given the dominant assumption within policy-making that the people brought together in these events must constitute a representative sample of the wider population? To improve the prospects for public dialogue and clarify what it can contribute to policy-making, this report explores ‘who or what is the public’ to make better sense of why and when public dialogue is carried out.